A study of a dynamic scheduling mechanism to guarantee QoS - Laalaoua, Rachid; Atmaca, Tulin (Communications - Scientific letters of the University of Zilina, 2000)
Packet scheduling is one of the key mechanisms that will be used in network elements (switches and routers) for supporting real-time applications in broadband networks. Provision of Quality-of-Service (QoS) guarantees is an important and challenging issue in the design of integrated service packet networks. Scheduling disciplines are an integral part of the problem and are closely related to other aspects of network modeling such as traffic charaterization and QoS specification. In this paper we discuss two priority scheduling mechanisms: Head of Line (HoL) and preemptive discipline; for both, we propose an analytical description and present numerical results obtained by Markov chain. A novel mechanism called Dynamic-Weighted Fair Queuing (Dynamic-WFQ) which depends on the Classes of Service and the queue occupancies is proposed. An example of selection function is solved by Markov Chain and the results are validated by simulation. Finally, we compare the performance evaluation of multimedia communication scheduling algorithms described above.